TRANSFORMING EXCELLENCE INTO INCLUSIVE: CASES FROM UNIVERSITIES IN THE USA, UK, SINGAPORE AND RUSSIA - Volosnikova, Lyudmila; Fedina, Lyudmila (SOCIETY. INTEGRATION. EDUCATION. Proceedings of the International Scientific Conference, 2020)
The article presents a semantic analysis of program documents of universities from different countries, who has leading positions in the QS-2018 ranking. The aim of this study is to provide a meaningful and semantic study of the development strategies of top universities in order to identify trends in the convergence of academic and inclusive excellence. The study conducted a content analysis of plans or strategies for the development of 4 universities: Massachusetts Institute of Technology (MIT, USA), University of Oxford (UO, UK), National University of Singapore (NUS, Singapore), Lomonosov Moscow State University (MSU, Russia). The content analysis criteria were refined indicators of diversity proposed in the model for Inclusive Excellence.The results showed that all program documents identify the basic values of inclusive excellence as the main ones: internationalization, activity, support, development, and others. Inclusive and academic excellence is formed in an environment where the main value and resource is the individual. Descriptors of criterions 1 and 2 are most common in the program documents of MIT and the UO. A comparative analysis of 4 documents showed that the strategy and models of inclusive and academic excellence reflect the unique track of development of the University and the country in which they are implemented.